2019
DOI: 10.1371/journal.pone.0212370
|View full text |Cite
|
Sign up to set email alerts
|

Familial multifocal micronodular pneumocyte hyperplasia with a novel splicing mutation in TSC1: Three cases in one family

Abstract: Multifocal micronodular pneumocyte hyperplasia (MMPH) is a rare pulmonary disease, generally manifesting as a tuberous sclerosis complex (TSC), characterised by multiple, small ground-glass nodular shadows on chest computed tomography (CT). Histological examination typically reveals multicentric, well-demarcated, nodular type II pneumocystic growth. Herein, we describe three cases of this rare pulmonary disease occurring within one family. Using reverse transcription polymerase chain reaction (RT-PCR) and dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…In fact, of the 17 patients with liver AML, 15 had renal AML, and eight had a score of 3 for severe renal AML ( Supplementary Table S1 ). Although there are few reports on MMPH, we previously reported that LOH occurs in lesions [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, of the 17 patients with liver AML, 15 had renal AML, and eight had a score of 3 for severe renal AML ( Supplementary Table S1 ). Although there are few reports on MMPH, we previously reported that LOH occurs in lesions [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that hamartomas associated with TSC, such as lymphangioleiomyomatosis (LAM), AML, and subependymal giant cell astrocytomas, are caused by mTOR activation with decreased or absent expression of TSC1/2 genes [ 7 , 8 ] and can be treated with mTOR inhibitors [ [9] , [10] , [11] ]. Loss of heterozygosity for TSC1/2 genes and high expression of phospho-p70S6K and phospho-4E-BP1 proteins observed in MMPH lesions suggest the activation of mTOR pathway and plausibility of a response to mTOR inhibitors [ 2 , 12 ]. In addition, mTOR inhibitors improve seizures in TSC, as observed in this case [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by multiple solid nodules or nodular ground-glass opacities (GGOs) observed on CT, randomly distributed throughout the lungs ( 9 ). Histologically, MMPH refers to multicentric and well-demarcated nodular growth of type II pneumocytes ( 10 ). Therefore, the differential diagnosis should consider atypical adenomatous hyperplasia, adenocarcinoma, pulmonary metastases, tuberculosis, sarcoidosis, and histiocytosis X.…”
Section: Discussionmentioning
confidence: 99%